2014
DOI: 10.1590/0104-07072014001650013
|View full text |Cite
|
Sign up to set email alerts
|

The practice of family health strategy workers when caring for women in gender violence situations

Abstract: The aim of the present study was to describe the practice of Family Health Strategy workers when dealing with women in gender violence situations. It is a qualitative study, conducted with 25 healthcare workers from three Family Health Strategy units in a municipality of the state of Bahia, Brazil. Data were collected through a semi-structured interview and analyzed based on the discourse analysis method. The results yielded two empirical categories: expression of violence against women due to gender issues, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
6

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 11 publications
0
12
0
6
Order By: Relevance
“…In this sense, the health sector needs to know the responsibilities of the professionals and services that may be part of the health care network in order to establish communication with the social equipment beyond its area of coverage, reaching other resources of the community (10)(11) . According to testimonies of the health professionals, the limitations of the network in the studied scenario are related to the services that operate in an uncoordinated way.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this sense, the health sector needs to know the responsibilities of the professionals and services that may be part of the health care network in order to establish communication with the social equipment beyond its area of coverage, reaching other resources of the community (10)(11) . According to testimonies of the health professionals, the limitations of the network in the studied scenario are related to the services that operate in an uncoordinated way.…”
Section: Discussionmentioning
confidence: 99%
“…Following these findings, a study pointed out that besides the identification of the violence experienced by the women, the actions of the health professionals should include the initial support to them with subsequent referral to other services (3) . However, the act of referring women to other services may be a way for health professionals to get rid of the problem (10) , leading to revictimization. This revictimization occurs because women in situations of violence need to report again their experience to each service or professional.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Quanto (11) Texto e contexto de Enfermagem (Jequié -Bahia) Qualitativa (n=25 profissionais de saúde)…”
Section: Resultsunclassified
“…18 A research showed that confronting gender-based violence by female (and male) ESF staff seemed like it was limited to a discussion about actions by the team, which did not involve women, in view the motivation of a proactive attitude and the citizenship practice. 19 In this context, it is important to reflect about the complexity of violence, crossing generations and unfoldings related to life and health conditions, demanding a closer look by public policies and the assistential network for both these demands.…”
Section: ] (E11 Sister)mentioning
confidence: 99%